PELAKSANAAN PENGOLAHAN PELAPORAN MORBIDITAS DAN MORTALITAS PASIEN RAWAT INAP (RL 4a) DI RSUD SLEMAN - , RESA SEPTI DIANI, Arief Kurniawan., SKM. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : The implementation of an external reporting in the Provincial Hospital of Sleman starting in 2013 have switched from SIRS revision revision SIRS V to VI. One of the hospital's external reporting is reporting morbidity and mortality inpatients (RL 4a). In the process of making reporting RL 4a in Sleman HOSPITALS still have constraints. One of the constraints in the processing file is reporting RL 4a inpatient medical record that has not been filled. Purpose : Knowing the implementation of reporting morbidity and mortality inpatients (RL 4a) as well as the constraints in making reporting morbidity and mortality inpatients (RL 4a) at the Provincial Hospital of Sleman. Methode : This study used a descriptive research with a qualitative approach and data collection are cross-sectional. Subjects in this study is the reporting officer morbidity inpatients, while the study object is the activity at the reporting morbidity and mortality of hospitalized patients. Techniques of data collection: interviews, documentation and observation studies. Results : making reporting morbidity and mortalitas hospitalized patients consisting of data, data processing and the presentation of data. Data in reporting morbidity and mortalitas hospitalized patients is the beam rollin medical patient inpatient. Data processing already computerized is coding, index, registers inpatient, as for making report morbidity and mortalitas hospitalized patients still manual. Presentation of data report data the state of morbidity and mortalitas hospitalized patients (RL 4a) in form of the table. Constraint in the manufacture of reporting morbidity and mortalitas hospitalized patients, obtainable are still many of the documents rollin medical that have not been filled with complete. Of a bundle of medical rollin complete, that have not been filled impede in the process of data processing and presentation of data reporting RL 4a, so that the report RL 4a be incomplete, accurate and improper time.